Ghost carbonate in Archean granitoids marks a geodynamic transition in the Mesoarchean - Ya-Wen Zhang; Shui-Jiong Wang; Hao Wang; Bin Su; Béatrice Luais; Yu Wang; Hui-Min Yu; Da Wang; Stephen F. Foley; Xian-Hua Li (Lithos, 2026)

Experimental trace element partition coefficients for upper mantle pyroxenites coexisting with H2O with CO2, NaCl and NH3 fluids - Matthew J. M. Phillips; Svyatoslav S. Shcheka; Stephen F. Foley (Contributions to Mineralogy and Petrology, 2026)
Experimental determinations of trace element distribution between rocks/minerals and fluids at mantle pressures and temperatures have concentrated on eclogite and on fluids containing H 2 O with or without the addition of NaCl. Here we present data for websterite (pyroxenite) coexisting with five different fluids: H 2 O, H 2 O+CO 2 , H 2 O+NaCl, H 2 O+CO 2 +NaCl and H 2 O+NH 3 . All experiments were conducted at 1.5 GPa and 800˚C using glassy carbon fluid traps that were kept in a frozen state following experiments until trace elements in the fluid traps were analysed by laser cryoablation-ICP-MS. Results show that Rb, Ba, Sr, Pb and Li are fluid-mobile, with lower rock/fluid partition coefficients (D Rock/Fluid ) for all mixed fluids relative to pure H 2 O. Lowest values (0.0004–0.123) are found for H 2 O+NH 3 fluids. Almost all for the REE are 2 O+CO 2 +NaCl and H 2 O+NH 3 fluids, as are the HFSE, which also show lower D Rock/Fluid than for eclogites, with or without NaCl. Re and Pt are fluid-mobile, with D Re Pt and lowest values for both in H 2 O+CO 2 fluids. The first row transition elements show D-values ranging from 0.0004 to 2.88 with only 4 of 35 data points > 1. D Rock/Fluid increase in the order Cu Rock/Fluid ,particularly low-Al clinpyroxenes.

Modernizing America’s National Forest Inventory through a Third Blue Ribbon Panel - Aaron Weiskittel; Dale Hogg; John W. Coulston; Christopher W. Woodall; Holly L. Munro; Hailemariam Temesgen; Timothy Foley; Nathaniel Osborne; Nathaniel Naumann; James Rakestraw; John S. Gunn; Nadia Tase; et al. (Journal of Forestry, 2026)

A common mantle source for strongly silica-undersaturated magmas: Insights from Zn-Fe isotopes in kimberlites - Ronghua Cai; Andrea Giuliani; Paolo A. Sossi; Tian-Hao Wu; Yongsheng He; D. Graham Pearson; Stephen F. Foley; Jingao Liu (Earth and Planetary Science Letters, 2026)

Mg isotopes and in-situ Rb Sr dating reveal carbonate-rich and carbonate-poor sediments in mantle sources of lamproites beneath the North China Craton - Kaizhang Yu; Yongsheng Liu; Wei Chen; Chunfei Chen; Chutian Shu; Stephen F. Foley; Jixing Li; Zhaochu Hu (Chemical Geology, 2025)

Kamafugites - Francesca Innocenzi; Sara Ronca; Samuele Agostini; Vincenza Guarino; Stephen F. Foley; Michele Lustrino (Earth-Science Reviews, 2025)

Asthenospheric flow and lithospheric erosion driving the outward growth of the northeastern Tibetan Plateau - Chutian Shu; Xiaoping Long; Stephen F. Foley; Kaizhang Yu; Zhuoying Zhang; Zheng-Xiang Li; Luc S. Doucet; Qiang Xu (Science Bulletin, 2025)

Paleoproterozoic to Cambro-Ordovician crustal evolution in the northern Indian margin: Evidence from whole-rock geochemical, zircon U–Pb, Hf and O isotope signatures in the granitoids of Arunachal Himalaya, Northeast India - Bidyananda Maibam; Waikhom Nongdon; Pankaj Kumar; Yoann Gréau; Jasper Berndt; Stephen Foley; Atul Kumar Singh; Deeksha Khandelwal (Gondwana Research, 2025)

Chalcophile elements in post-subduction magmas and implications for metal recycling in oceanic and continental subduction - Xiang Wang; Zaicong Wang; Li-Qun Dai; Wen Zhang; Xiaodong Deng; Xi Zhang; Stephen Foley; Charles H. Langmuir; Wei Fang; Lang Wang; Tao He; Aiqing Ren; et al. (Geochimica et Cosmochimica Acta, 2025)

The mineralogical distribution of Ni in mantle rocks controls the fertility of magmatic Ni-sulfide systems - Daryl E. Blanks; David A. Holwell; Isra S. Ezad; Andrea Giuliani; Marco L. Fiorentini; Stephen F. Foley (Mineralium Deposita, 2025)
Mantle-derived mafic-ultramafic melts are the primary host for magmatic Ni-Cu-Co-PGE deposits. One common assumption about this mineral system is that Ni-fertility is a product of high-degree melting of anhydrous mantle peridotites, including a substantial contribution from olivine. However, in metasomatised mantle rocks, which partially melt at lower temperatures than anhydrous peridotites, Ni is hosted by a range of minerals, including hydrous phases such as phlogopite and amphibole in addition to olivine and orthopyroxene. The lower melting point of these hydrous phases makes Ni in phlogopite a potentially significant contributor to the Ni enrichment of mantle melts from metasomatised assemblages. We analyse a suite of phlogopite-bearing mantle rocks which display variably metasomatised assemblages using SEM mapping to quantify mineral assemblages, and laser ablation ICP-MS to determine the Ni deportment in these rocks. Phlogopite in hydrous peridotites contains 859–1126 ppm Ni equating to ~ 12% of the bulk Ni content in an assemblage containing 25% phlogopite. Mica-Amphibole-Rutile-Ilmenite-Diopside rocks contain phlogopite with 428–715 ppm Ni, which can contribute up to 50% of the bulk Ni in an assemblage of 30% phlogopite. At temperatures below the dry peridotite solidus (< 1300 °C), phlogopite can become a significant contributor of Ni to mantle melts. Thus, partial melting of metasomatised hydrous assemblages can produce Ni-fertile mafic-ultramafic magmas without substantial temperature perturbations such as those associated with mantle plumes. This opens up a range of geodynamic settings for Ni sulfide fertility, away from large igneous provinces and their plumbing systems, into settings such as orogenic belts, arcs and intraplate rifts.

Impacts of mesoscale meteorology on the evolution of fluvial features in Lyot crater, Mars - Lori-Ann Foley; Stephen Lewis; Matt Balme; James Holmes (Icarus, 2025)

Hydrous minerals are sinks for first row transition elements in the mantle: An experimental partitioning study - Isra S. Ezad; Joshua J. Shea; Stephen F. Foley (Chemical Geology, 2025)

Melting of amphibole-apatite-rich metasomes in the continental mantle and comparison of melt compositions with natural igneous rocks - Stephen F. Foley; Isra S. Ezad; Chutian Shu; Michael W. Förster (Lithos, 2025)

Pre-Himalayan crustal evolution in the northern margin of India: Implications from zircon U–Pb, Hf and O isotope study of Chhota Shigri granitoids, Himachal Himalaya, Northwest India - Waikhom Nongdon; Bidyananda Maibam; Pankaj Kumar; Yoann Gréau; Jasper Berndt; Stephen Foley; Atul Kumar Singh; Deeksha Khandelwal (Gondwana Research, 2025)

Origin of Amphibole Cumulates at the Base of an Exposed Arc Crustal Section: Perspectives From Fiordland, New Zealand - Patrick Manselle; Stephen Foley; Nathan Daczko (Island Arc, 2025)
The formation of amphibole‐rich cumulates in arc settings plays a crucial role in influencing the chemistry of ascending arc magmas. However, understanding the processes of formation of these cumulates is challenging due to the subtle nature of their fractionation. This study presents new petrographic and geochemical analyses of amphibole‐rich cumulate rocks from outcrops across Fiordland, New Zealand, an exposed section of the lower arc crust. Our findings show two primary styles of formation. Style 1 represents direct fractionation from a melt, and is typified by adcumulate textures, similar rare earth element concentrations, and minor mineral phases. Style 2 amphiboles show greater variations in their rare earth element contents and typically lack adcumulate textures. Our results indicate that direct igneous fractionation from a melt is the primary formation mechanism for amphibole cumulates, with minor contributions from melt–rock interaction, aligning with the amphibole sponge model. This research underscores the significance of amphibole cumulate formation in the evolution of the lower crust in arc systems and illustrates how co‐crystallizing minerals and precursor assemblages can influence the chemistry of ascending magmas during metasomatism.

Compositional signatures of clinopyroxenes from the mafic rocks of the Nagaland ophiolite (NE India): Inferences for melting of diverse source regions in a transitional arc-type setting - Monica Wangjam; Bidyananda Maibam; Stephen Foley; Argyrios Kapsiotis (Geochemistry, 2024)

Recent advances made by reaction experiments on melting of heavily metasomatized hydrous mantle - Dejan Prelević; Michael W. Förster; Stephan Buhre; Fatma Gülmez; Tobias Grützner; Yu Wang; Stephen F. Foley (Earth-Science Reviews, 2024)

Melting behavior of impure limestone under H2O-poor conditions: Implications for the contribution of carbonate-rich sediments to arc magmatic carbon output - Juan Wang; Stephen Foley; Xiangfa Wang; Chao Wang; Yongsheng Liu (Chemical Geology, 2024)

Deep mantle cycle of chalcophile metals and sulfur in subducted oceanic crust - Zongqi Zou; Zaicong Wang; Yi-Gang Xu; Stephen Foley; Huai Cheng; Liang Ma; Xiang Wang; Kang Chen; Zhaochu Hu; Yongsheng Liu; Yanhong Liu (Geochimica et Cosmochimica Acta, 2024)

Fluid loss to the fore-arc controls the recycling efficiency of nitrogen in subduction zones - Michael W. Förster; Chunfei Chen; Stephen F. Foley; Olivier Alard; Gregory M. Yaxley (Chemical Geology, 2024)

Contrasting Cu isotopes in mid-ocean ridge basalts and lower oceanic crust: Insights into the oceanic crustal magma plumbing systems - Zongqi Zou; Zaicong Wang; Yi-Gang Xu; Jakub Ciazela; Xia Wang; Stephen Foley; Wei-Qi Zhang; Wei Li; Ming Li; Yongsheng Liu (Earth and Planetary Science Letters, 2024)

Lithospheric hydrous pyroxenites control localisation and Ni endowment of magmatic sulfide deposits - Isra S. Ezad; Daryl E. Blanks; Stephen F. Foley; David A. Holwell; Jason Bennett; Marco L. Fiorentini (Mineralium Deposita, 2024)

Carbonatite and ultrabasic magmatism at Toro Ankole and Virunga, western branch of the East African Rift system - Francesca Innocenzi; Sara Ronca; Stephen Foley; Samuele Agostini; Michele Lustrino (Gondwana Research, 2024)

Calcium isotope compositions of subduction-related leucite-bearing rocks: Implications for the calcium isotope heterogeneity of the mantle and carbonate recycling in convergent margins - Huange Ren; Martina Casalini; Sandro Conticelli; Chunfei Chen; Stephen F. Foley; Lanping Feng; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2024)

Calcium isotopes track volatile components in the mantle sources of alkaline rocks and associated carbonatites - Chunfei Chen; Stephen F. Foley; Sebastian Tappe; Huange Ren; Lanping Feng; Yongsheng Liu (Earth and Planetary Science Letters, 2024)

Origin of carbonate melts in orogenic belts by anatexis of downthrust carbonate sediments - Chengyuan Wang; Stephen F. Foley; Yongsheng Liu; Yu Wang; Yi-Gang Xu (Earth and Planetary Science Letters, 2023)

Tightly coupled Ca-Zn-Sr isotope co-variations in basalts caused by recycled calcium carbonate in the mantle source - Detao He; Yongsheng Liu; Frédéric Moynier; Stephen F. Foley; Chunfei Chen; Yangtao Zhu; Xinting Lü; Ganglan Zhang; Keqing Zong (Chemical Geology, 2023)

Volcanic phosphorus supply boosted Mesozoic terrestrial biotas in northern China - Chao Ma; Yanjie Tang; Ross N. Mitchell; Yongfei Li; Shouliang Sun; Jichang Zhu; Stephen F. Foley; Min Wang; Chenyang Ye; Jifeng Ying; Rixiang Zhu (Science Bulletin, 2023)

Comparing travel behaviour characteristics and correlates between large and small Kenyan cities (Nairobi versus Kisumu) - Lambed Tatah; Louise Foley; Tolu Oni; Matthew Pearce; Charles Lwanga; Vincent Were; Felix Assah; Yves Wasnyo; Ebele Mogo; Gabriel Okello; Stephen Mogere; Charles Obonyo; et al. (Journal of Transport Geography, 2023)

Transition from tholeiitic to alkali basalts via interaction between decarbonated eclogite-derived melts and peridotite - Qiuhong Xie; Zhaochong Zhang; Stephen F. Foley; Chunfei Chen; Zhiguo Cheng; Yu Wang; Weiliang Kong; Yiwen Lv; M. Santosh; Qizhen Jin; Lukáš Krmíček; Xiangkun Zhu (Chemical Geology, 2023)

Dating blueschist-facies metamorphism within the Naga ophiolite, Northeast India, using sheared carbonate veins - Bidyananda Maibam; Richard M. Palin; Axel Gerdes; Richard W. White; Stephen Foley (International Geology Review, 2023)

Application of Ge/Si ratios to ultramafic alkaline rocks using a novel LA-ICP- MS/MS method - Matthew J.M. Phillips; Stephen F. Foley; Olivier Alard (Chemical Geology, 2023)

The effect of COH fluids on partial melting of eclogite and lherzolite under moderately oxidizing and reducing conditions - Zairong Liu; Arno Rohrbach; Carla Tiraboschi; Stephen F. Foley; Jasper Berndt; Stephan Klemme (Chemical Geology, 2023)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Insights into the petrogenesis of the West Kimberley lamproites from trace elements in olivine - A. Lynton Jaques; Stephen F. Foley (Mineralogy and Petrology, 2018)

Petrology of spinel lherzolite xenoliths from Youkou volcano, Adamawa Massif, Cameroon Volcanic Line: mineralogical and geochemical fingerprints of sub-rift mantle processes - Merlin Patrick Wagsong Njombie; Robert Temdjim; Stephen F. Foley (Contributions to Mineralogy and Petrology, 2018)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Trace element variations in olivine phenocrysts from Ugandan potassic rocks as clues to the chemical characteristics of parental magmas - Stephen F. Foley; Dorrit E. Jacob; Hugh St. C. O’Neill (Contributions to Mineralogy and Petrology, 2011)

Continuous cratonic crust between the Congo and Tanzania blocks in western Uganda - Klemens Link; Daniel Koehn; Matthias G. Barth; John V. Tiberindwa; Erasmus Barifaijo; Kevin Aanyu; Stephen F. Foley (International Journal of Earth Sciences, 2010)

Trace element partitioning in the granulite facies - Franziska Nehring; Stephen F. Foley; Pentti Hölttä (Contributions to Mineralogy and Petrology, 2010)

A model of carbon evasion and sedimentation in temperate lakes - Paul C. Hanson; Amina I. Pollard; Darren L. Bade; Katie Predick; Stephen R. Carpenter; Jonathan A. Foley (Global Change Biology, 2004)
Lakes process terrigenous carbon. The carbon load processed by lakes may partially offset estimates made for terrestrial net ecosystem exchange ( NEE ). The balance within lakes between carbon burial and evasion to the atmosphere determines whether lakes are net sinks or net sources of atmospheric carbon. Here we develop a model to study processing of both autochthonous and allochthonous carbon sources in lakes. We run the model over gradients of dissolved organic carbon ( DOC ) and total phosphorus ( TP ) concentrations found in the Northern Highlands Lake District of Wisconsin. In our model, lakes processed between 5 and 28 g C m −2 (watershed) yr −1 derived from the watershed, which approximates one‐tenth of NEE for similar terrestrial systems without lakes. Most lakes were net heterotrophic and had carbon evasion in excess of carbon burial, making them net sources of carbon to the atmosphere. Only lakes low in DOC and moderate to high in TP were net autotrophic and net sinks of carbon from the atmosphere.

The effect of crystal orientation on the wetting behaviour of silicate melts on the surfaces of spinel peridotite minerals - Frank Schäfer; Stephen Foley (Contributions to Mineralogy and Petrology, 2002)

Global response of terrestrial ecosystem structure and function to CO 2 and climate change: results from six dynamic global vegetation models - Wolfgang Cramer; Alberte Bondeau; F. Ian Woodward; I. Colin Prentice; Richard A. Betts; Victor Brovkin; Peter M. Cox; Veronica Fisher; Jonathan A. Foley; Andrew D. Friend; Chris Kucharik; Mark R. Lomas; et al. (Global Change Biology, 2001)
Summary The possible responses of ecosystem processes to rising atmospheric CO 2 concentration and climate change are illustrated using six dynamic global vegetation models that explicitly represent the interactions of ecosystem carbon and water exchanges with vegetation dynamics. The models are driven by the IPCC IS92a scenario of rising CO 2 ( Wigley et al . 1991 ), and by climate changes resulting from effective CO 2 concentrations corresponding to IS92a, simulated by the coupled ocean atmosphere model HadCM2‐SUL. Simulations with changing CO 2 alone show a widely distributed terrestrial carbon sink of 1.4–3.8 Pg C y −1 during the 1990s, rising to 3.7–8.6 Pg C y −1 a century later. Simulations including climate change show a reduced sink both today (0.6–3.0 Pg C y −1 ) and a century later (0.3–6.6 Pg C y −1 ) as a result of the impacts of climate change on NEP of tropical and southern hemisphere ecosystems. In all models, the rate of increase of NEP begins to level off around 2030 as a consequence of the ‘diminishing return’ of physiological CO 2 effects at high CO 2 concentrations. Four out of the six models show a further, climate‐induced decline in NEP resulting from increased heterotrophic respiration and declining tropical NPP after 2050. Changes in vegetation structure influence the magnitude and spatial pattern of the carbon sink and, in combination with changing climate, also freshwater availability (runoff). It is shown that these changes, once set in motion, would continue to evolve for at least a century even if atmospheric CO 2 concentration and climate could be instantaneously stabilized. The results should be considered illustrative in the sense that the choice of CO 2 concentration scenario was arbitrary and only one climate model scenario was used. However, the results serve to indicate a range of possible biospheric responses to CO 2 and climate change. They reveal major uncertainties about the response of NEP to climate change resulting, primarily, from differences in the way that modelled global NPP responds to a changing climate. The simulations illustrate, however, that the magnitude of possible biospheric influences on the carbon balance requires that this factor is taken into account for future scenarios of atmospheric CO 2 and climate change.

Phase relations and fractionation sequences in potassic magma series modelled in the system CaMgSi 2 O 6 -KAlSiO 4 -Mg 2 SiO 4 -SiO 2 -F 2 O −1 at 1 bar to 18 kbar - Stefan Melzer; Stephen F. Foley (Contributions to Mineralogy and Petrology, 2000)